2016
DOI: 10.3390/ijms17050652
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous and Endogeneous Disialosyl Ganglioside GD1b Induces Apoptosis of MCF-7 Human Breast Cancer Cells

Abstract: Gangliosides have been known to play a role in the regulation of apoptosis in cancer cells. This study has employed disialyl-ganglioside GD1b to apoptosis in human breast cancer MCF-7 cells using exogenous treatment of the cells with GD1b and endogenous expression of GD1b in MCF-7 cells. First, apoptosis in MCF-7 cells was observed after treatment of GD1b. Treatment of MCF-7 cells with GD1b reduced cell growth rates in a dose and time dependent manner during GD1b treatment, as determined by XTT assay. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…4). In contrast, the ER positive (+) MCF-7 cells (ER+) 2 showed the increased expression level of ICAM-1. This clearly suggested that the estrogen receptor is indeed a co-regulator to regulate the ICAM-1 expression with GD3 to GD2 conversion in human breast cancer cells.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…4). In contrast, the ER positive (+) MCF-7 cells (ER+) 2 showed the increased expression level of ICAM-1. This clearly suggested that the estrogen receptor is indeed a co-regulator to regulate the ICAM-1 expression with GD3 to GD2 conversion in human breast cancer cells.…”
Section: Discussionmentioning
confidence: 92%
“…3A, B, C, D, E), suggesting that over-expression of GD3 synthase suppresses invasion activity by down-regulation of ICAM-1. Interestingly, when SK-BR3 cells were used as another type of ER negative human breast cancer cell line, the SK-BR3 (ER-) cells exhibited the reduced level of ICAM-1 expression likely to MDA-MB231 cells, which are also ER negative breast cancer cells 2 (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations